Fundamentals of financial management - Brigham, Eugene F. (Cengage Learning, 2019)
This book provides the basic information about financial management such as introduction, concepts in financial management, financial assets, capital bugeting, capital structure and dividend policy, working capital management and financial and some special topics in this field.